2017
DOI: 10.1186/s12863-017-0481-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of effector-like proteins in Trichoderma spp. and role of a hydrophobin in the plant-fungus interaction and mycoparasitism

Abstract: Background Trichoderma spp. can establish beneficial interactions with plants by promoting plant growth and defense systems, as well as, antagonizing fungal phytopathogens in mycoparasitic interactions. Such interactions depend on signal exchange between both participants and can be mediated by effector proteins that alter the host cell structure and function, allowing the establishment of the relationship. The main purpose of this work was to identify, using computational methods, candidates of effector prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 96 publications
3
82
0
Order By: Relevance
“…During T. virens and A. thaliana interactions, we observed that, even before there was physical contact between both participants, the expression of TvCyt2 was down-regulated, subsequently increasing until reaching the basal expression levels observed in the control condition. This behavior in gene expression has been observed in epl1 and Tatrx2 genes reported by Guzmán-Guzmán et al (2017). Moreover, a transcriptomic analysis of T. atroviride in interactions with A. thaliana showed a larger number of downregulated genes than upregulated genes, suggesting that the presence of the plant provides signals participating in the downregulation of some genes normally expressed in the vegetative state, thus starting a chemical communication that contributes to the establishment of the symbiosis (A. Herrera-Estrella personal communication).…”
Section: Discussionsupporting
confidence: 57%
“…During T. virens and A. thaliana interactions, we observed that, even before there was physical contact between both participants, the expression of TvCyt2 was down-regulated, subsequently increasing until reaching the basal expression levels observed in the control condition. This behavior in gene expression has been observed in epl1 and Tatrx2 genes reported by Guzmán-Guzmán et al (2017). Moreover, a transcriptomic analysis of T. atroviride in interactions with A. thaliana showed a larger number of downregulated genes than upregulated genes, suggesting that the presence of the plant provides signals participating in the downregulation of some genes normally expressed in the vegetative state, thus starting a chemical communication that contributes to the establishment of the symbiosis (A. Herrera-Estrella personal communication).…”
Section: Discussionsupporting
confidence: 57%
“…Brotman et al, 2008;Morán-Diez et al, 2009;Salas-Marina et al, 2015). Importantly, some of these MAMPs are also proteins (swollenins, endopolygalacturonases, and hydrophobins) that work as colonization factors (Brotman et al, 2008;Morán-Diez et al, 2009;Guzmán-Guzmán et al, 2017) or help the fungus to tolerate antimicrobial compounds accumulated by the plant (Ruocco et al, 2009). Here, Dhda-2 was affected in its capability to induce the SAR and ISR in Arabidopsis, probably as a consequence of its impairment to colonize Arabidopsis roots, and therefore was unable to induce protection against the biotrophic and necrotrophic pathogens Pst DC3000 and B. cinerea.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Zymoseptoria tritici ribonuclease effector Zt6 was shown to display both phytotoxic as well as antimicrobial activity , providing first experimental evidence for a class of effector proteins required for plant colonisation as well as microbeÀmicrobe interactions. Similarly, the gene tvhydii1 of Trichoderma virens, encoding a class II hydrophobin, is expressed during Arabidopsis thaliana root colonisation as well as confrontation with the phytopathogen Rhizoctonia solani (Guzman-Guzman et al, 2017). Moreover, putative effector genes of the mycoparasite Pseudozyma flocculosa are specifically expressed during colonisation of the phytopathogen Blumeria graminis (Laur et al, 2018).…”
Section: Introductionmentioning
confidence: 99%